Effects of Skipping Rope Training and Running on Cardiovascular Risk Indicators in Overweight and Obese Girls - Roya Gharaeinejad; Amir Hossein Haghighi; Roya Askari; Hadi Shahrabadi (علوم بهداشتی ایران)
Background and Purpose: The prevalence of overweight and obesity among adolescents is high. It is necessary to find the methods to reduce the complications of obesity. This study aims to investigate the effect of skipping rope training (SRT) compared to running training (RT) on some cardiovascular risk indicators in overweight/obese girls. Materials and Methods: In this quasi-experimental study that was conducted in 2020 in Neyshabur, Iran, 30 overweight/obese girls were randomly divided into two training groups (SRT and RT) and one control group. The training programs were performed for 8 weeks at three sessions per week. RT program consisted of running with one-minute intervals and an intensity of 70-75% HRmax. The SRT program was performed with one-minute intervals and an intensity of 45 jumps per minute. The data were analyzed using repeated measures ANOVA and Bonferroni’s post hoc test in SPSS software, version 23. The significance level was set at 0.05. Results: There was no significant difference between the two groups of SRT and RT in the indices (P>0.05); however, body weight (-5.13%), body mass index (BMI) (-8.16%), maximum oxygen uptake (VO2max; 18.18%), triglyceride (-27.45%) and apolipoprotein A1 (apoA1; 2.53%) had a significant improvement in the SRT group compared to the control group (P<0.05). In the RT group, only the VO2max (18.83%) had a significant improvement compared to the control group (P<0.01). Conclusion: Both SRT and RT seem to have a role in improving cardiovascular risk indicators.